2018
DOI: 10.1242/jeb.185074
|View full text |Cite
|
Sign up to set email alerts
|

Dietary canthaxanthin reduces xanthophyll uptake and red coloration in adult red-legged partridges

Abstract: Carotenoids give color to conspicuous animal signals that are often the product of sexual selection. Knowledge of the mechanisms involved in carotenoid-based signaling is critical to understanding how these traits evolve. However, these mechanisms remain only partially understood. Carotenoids are usually viewed as scarce dietary antioxidants whose allocation to ornaments may trade off against health. This trade-off would ensure its reliability as a signal of individual quality. In the case of red (keto)caroten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…2013) and Alonso‐Alvarez et al. (2018)’s protocols with some modifications (more details in Supporting Information). Standards of lutein, zeaxanthin, canthaxanthin, astaxanthin, 3HOE, β‐cryptoxanthin, and β‐carotene were purchased from CaroteNature (Lupsingen, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…2013) and Alonso‐Alvarez et al. (2018)’s protocols with some modifications (more details in Supporting Information). Standards of lutein, zeaxanthin, canthaxanthin, astaxanthin, 3HOE, β‐cryptoxanthin, and β‐carotene were purchased from CaroteNature (Lupsingen, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…Carotenoids are a pigment class that is responsible for a wide range of colors in plant and animal species and figure prominently among other pigments as an important antioxidant primarily derivable from marine species [7]. It has been shown that dietary supplementation of canthaxanthin, a common carotenoid, in aquaculture salmon and trout could color the fillet with red-pink color [8,9] and that pigmentation intensity of rainbow trout flesh was positively correlated with added canthaxanthin in fish feed [10].…”
Section: Introductionmentioning
confidence: 99%
“…Familiar names of this colouring are canthaxanthin, food orange 8, canthaxanthin (Bendich et al, 2006). Usually, E161g is a crystalline powder or crystals of intense violet colour (Surai, 2012;Alonso-Alvarez et al, 2018). In solution it obtains tones ranging from orange to red.…”
Section: Introductionmentioning
confidence: 99%